Effect of coal type on aerosol optical properties at Ulaanbaatar city - Narangarav Tumur-Uyal; Baatarchuluun Tsermaa; Tuvshinjargal Baldorj; Javzandolgor Bad; Daariimaa Badarch (Proceedings of the Mongolian Academy of Sciences)
In this study, seasonal characteristics of aerosol optical properties at Ulaanbaatar station of the international network of SKYNET are investigated using ground-based skyradiometer from the years extending from 2017 to 2023. The aerosol optical thickness (AOT) at 500nm wavelength and Angstrom exponent (AE) were determined in winter to evaluate the decrease in air pollution in Ulaanbaatar since implementing the government's decision to use coal briquettes for household heating. During the study period, the monthly mean AOT at 500nm varied throughout the year, with the maximum value of 0.178±0.004 obtained in winter due to households burning large amounts of biomass, and the highest AOT (0.183) was obtained in February. The mean AOT was 0.21 in the winter of 2017-2019, which decreased by 15 per cent to 0.18 in the winter of 2019-2023.